The use of process benchmarking in the water industry to introduce changes in the digitization of the company’s value chain - Natalia R. Potoczek (Journal of Entrepreneurship, Management and Innovation)
PURPOSE: The review of the literature and numerous online sources, in particular the information platforms of international organizations supporting the activities of the water sector, was aimed at verifying research experiences in the field of digital maturity of enterprises, identifying research approaches used in benchmarking water utilities, and determining the level of interest in the analysis of the water supply industry value chain. It was found that there is no benchmarking methodology that would enable the observation of changes in the business processes of water supply companies under the influence of digital technologies. Therefore, this article presents a framework for benchmarking the digitization of business processes. The article also presents the premises for benchmarking the digitization of processes included in the value chain of a water supply company and the benefits of including digital technologies supporting processes from an economic, social, and environmental perspective. One of the key stages of creating the concept of benchmarking research is creating a matrix of variables relating to the objectives pursued by water supply companies. METHODOLOGY: The proposed concept of benchmarking the digitization of business processes included in the value chain of a water utility company was prepared based on literature studies and analysis of selected internet platforms of international organizations operating in the water sector. FINDINGS: The analysis of the decomposition of the enterprise value chain, the criteria, and levels of process maturity assessment, and the latest digital technologies made it possible to prepare two scenarios of the benchmarking stages of processes and use digital technologies depending on the level of process maturity and benchmarking experience. IMPLICATIONS FOR THEORY AND PRACTICE: The proposed model is highly conceptual and requires validation in pilot studies to verify the levels of decomposition of the value chain, to select key digital technologies for research and to determine the scale of digital maturity for each of the technologies included in the study. Organizations conducting benchmarking research can broaden the scope of their research and provide water utilities with information on the latest digital technologies supporting business processes. ORIGINALITY AND VALUE: Using value chain taxonomy to assess the support of business processes by digital technologies is an original approach. It enables the acquisition of knowledge about the importance of digital technologies in all processes carried out in the enterprise.